2008
DOI: 10.1093/pcp/pcn105
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Heat Shock Factor HsfA1a-Binding Sites in vivo Revealed Variations of Heat Shock Elements in Arabidopsis thaliana

Abstract: The information about DNA-binding sites of regulatory protein is important to understanding the regulatory network of DNA-protein interactions in the genome. In this report we integrated chromatin immunoprecipitation with DNA cloning to isolate genomic sites bound in vivo by heat shock factor HsfA1a in Arabidopsis thaliana. Plantlets were subjected to formaldehyde crosslinking, followed by immunoprecipitation of chromatin. The immunoprecipitated DNA was amplified by PCR and cloned. From a library enriched in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 30 publications
2
77
0
Order By: Relevance
“…22) In fact, Hsf-dependent expression of HSresponsive genes is required for cooperation between HSE and CCAAT-box. 23) Recently, Guo et al 24) reported that HsfA1a bound the stress responsive element (STRE: AGGGG). However, the present experiments showed that only HSE modules of target genes were essential for transcriptional activation by HsfA2, suggesting that other cis elements are not required.…”
Section: Resultsmentioning
confidence: 99%
“…22) In fact, Hsf-dependent expression of HSresponsive genes is required for cooperation between HSE and CCAAT-box. 23) Recently, Guo et al 24) reported that HsfA1a bound the stress responsive element (STRE: AGGGG). However, the present experiments showed that only HSE modules of target genes were essential for transcriptional activation by HsfA2, suggesting that other cis elements are not required.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of Hsps as chaperones, including Hsp18.2 and Hsp70, protects cells against injuries associated with various stressors (Simões-Araújo et al, 2003;de Azevedo et al, 2012;Magdalena et al 2012). On the other hand, HsfA1a can bind various promoter targets that are not limited to classical Hsp genes and also include other genes (Guo et al, 2008), implying a broad physiological basis for the stress tolerance role of HsfA1a. However, determining the exact genome-wide target genes of individual HsfA1 members, and whether target genes regulated by HsfA1a in response to distinct stressors are identical or only partially overlap require further investigation.…”
Section: A B C Discussionmentioning
confidence: 99%
“…For the sorbitol treatment, sorbitol was added into the SIB buffer to a final concentration of 1 M, followed by incubation at room temperature for 20 min under vacuum. The stressed plants were subjected to formaldehyde crosslinking/chromatin immunoprecipitation (X-Chip) using HsfA1a antibodies, and the immunoprecipitated DNA was analyzed by PCR using primer pairs specific to HSP18.2 and HSP70 gene promoters, according to Guo et al (2008). A primer pair amplifying a far upstream sequence of the HSP18.2 promoter was used as a negative control.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…Class B and C Hsfs lack the AHA motif and have no activator function on their own (Döring et al, 2000;Nover et al, 2001;Kotak et al, 2004). It has been demonstrated that HsfA1a and other plant Hsf members bind the heat shock element (HSE) consisting of tandem inverted repeats of the short consensus sequence nGAAn (nTTCnnGAAnnTTCn, called the perfect HSE) and the AGGGG motif (von Guo et al, 2008). The roles of several Hsfs of class A (15 members) in Arabidopsis that show high functional diversification and genetic redundancy are still unknown, and the key elements mediating HsfA1 genes in the thermotolerance remain obscure.…”
Section: Introductionmentioning
confidence: 99%